2002
DOI: 10.1128/iai.70.3.1056-1068.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Immunization Using Colonization Factor and Heat-Labile Enterotoxin Induces Correlates of Protective Immunity for EnterotoxigenicEscherichia coli

Abstract: Enterotoxigenic Escherichia coli (ETEC) diarrheal disease is a worldwide problem that may be addressed by transcutaneous delivery of a vaccine. In several human settings, protective immunity has been associated with immune responses to E. coli colonization factors and to the heat-labile toxin that induces the diarrhea. In this set of animal studies, transcutaneous immunization (TCI) using recombinant colonization factor CS6 and cholera toxin (CT) or heat-labile enterotoxin (LT) as the adjuvant induced immunogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
54
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 52 publications
5
54
0
Order By: Relevance
“…Whereas several previous studies demonstrate expansion of antigen-specific CD8 T cells after EPI, most focused on responses early after immunization and/or did not evaluate induction of protective responses against pathogens (4-7). Our finding that EPI using the ADP ribosylating exotoxin CT evokes optimal CD8 T-cell responses (in terms of magnitude, durability, and functional efficacy) parallel work in mice and humans that exploit CT and the related toxin LT (4,10,(13)(14)(15). In agreement with previous studies (6, 7), we found that CpG could also prime CD8 T cells via EPI, although the responses induced with this adjuvant did not persist to generate protective memory.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Whereas several previous studies demonstrate expansion of antigen-specific CD8 T cells after EPI, most focused on responses early after immunization and/or did not evaluate induction of protective responses against pathogens (4-7). Our finding that EPI using the ADP ribosylating exotoxin CT evokes optimal CD8 T-cell responses (in terms of magnitude, durability, and functional efficacy) parallel work in mice and humans that exploit CT and the related toxin LT (4,10,(13)(14)(15). In agreement with previous studies (6, 7), we found that CpG could also prime CD8 T cells via EPI, although the responses induced with this adjuvant did not persist to generate protective memory.…”
Section: Discussionsupporting
confidence: 82%
“…Our data extend previous reports on the potency of CT and the related exotoxin LT in epicutaneous priming of cellular and humoral responses in mice and humans (12)(13)(14)(15), but raised the question of how CT confers its adjuvant effects. Most adjuvants induce "danger" signals to activate the innate immune response through pattern recognition receptors (PRRs) (19).…”
Section: Epicutaneous Vaccination Using Cpg and Cholera Toxin As Adjusupporting
confidence: 73%
See 1 more Smart Citation
“…TCI in the presence of CT as adjuvant after hydration was reported to generate Th responses. [15][16][17] CT leads to activation of LCs after topical application, indicated by the increased expression of CD11c, ICAM-1 and MHC class II molecules and by morphologic changes such as rounding and loss of dendrites. 48 Moreover, CT induces LC migration to draining lymph nodes even after application to intact skin.…”
Section: Discussionmentioning
confidence: 99%
“…This kind of pretreatment of the skin leads to development of humoral 13,14 and Th responses after TCI with proteins or peptides. [15][16][17] Another way of antigen entry through the skin is uptake via noncornified epithelial cells of the HF. Wax depilation induces development of homogenous anagen phase, which is accompanied by a locally increased number of LCs.…”
mentioning
confidence: 99%